2011
DOI: 10.1007/s00415-011-6031-z
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic small fiber neuropathy in diabetes mellitus: investigations with intraepidermal nerve fiber density, quantitative sensory testing and laser-evoked potentials

Abstract: This study aimed at evaluating the performance of a battery of morphological and functional tests for the assessment of small nerve fiber loss in asymptomatic diabetic neuropathy (DNP). Patients diagnosed for ≥10 years with type 1 (n = 10) or type 2 (n = 13) diabetes mellitus (DM) without conventional symptoms or signs of DNP were recruited and compared with healthy controls (n = 18) and patients with overt DNP (n = 5). Intraepidermal nerve fiber density (IENFd) was measured with PGP9.5 immunostaining on punch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…A recent study showed abnormal LEPs in a subgroup of 29 patients with painful peripheral neuropathy associated to hepatitis C virus, in contrast to normal sensory action potentials and intra-epidermal nerve fibre density 32. A comparative study including punch skin biopsies, QST and LEPs showed that the latter presented the highest specificity (83%) and sensitivity (91%) in detecting asymptomatic diabetic neuropathy in the distal leg in a cohort of 23 patients with a disease duration of >10 years 33. Taking these observations into account, a three-step diagnostic approach is recommended: (1) QST and nerve conduction studies and, if negative, followed by (2) LEPs and finally by (3) punch skin biopsy.…”
Section: Pain-related Laser Evoked Potentials (Leps)mentioning
confidence: 95%
“…A recent study showed abnormal LEPs in a subgroup of 29 patients with painful peripheral neuropathy associated to hepatitis C virus, in contrast to normal sensory action potentials and intra-epidermal nerve fibre density 32. A comparative study including punch skin biopsies, QST and LEPs showed that the latter presented the highest specificity (83%) and sensitivity (91%) in detecting asymptomatic diabetic neuropathy in the distal leg in a cohort of 23 patients with a disease duration of >10 years 33. Taking these observations into account, a three-step diagnostic approach is recommended: (1) QST and nerve conduction studies and, if negative, followed by (2) LEPs and finally by (3) punch skin biopsy.…”
Section: Pain-related Laser Evoked Potentials (Leps)mentioning
confidence: 95%
“…However, the abnormalities are not as extensive as in patients with classical disease (Biegstraaten et al 2011(Biegstraaten et al , 2012 and predominantly concern small nerve fibre structure as represented by the IENFD. Similarly, in patients with diabetes mellitus (DM), an abnormal IENFD in the distal leg and impaired cold sensation have been found, even without neuropathic symptoms (Umapathi et al 2007;Loseth et al 2008;Ragé et al 2011). For both DM and nonclassical FD, it may be hypothesized that a reduced IENFD and abnormal QST modalities reflect a presymptomatic state.…”
Section: Discussionmentioning
confidence: 99%
“…References and inclusion criteria can be obtained from previously published work [6,51]. Written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…The Toronto Clinical Scoring System (TCSS) was used to screen for diabetic neuropathy. None of the control subjects had a history of alcohol or drug abuse, significant illnesses, or clinical findings suggestive of peripheral or central nervous system disorders [51]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation